2016
DOI: 10.1186/s12862-016-0678-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary histories determine DNA barcoding success in vascular plants: seven case studies using intraspecific broad sampling of closely related species

Abstract: BackgroundFour plastid regions, rpoB, rpoC1, matK, and trnH-psbA, have been recommended as DNA barcodes for plants. Their success in delimiting species boundaries depends on the existence of a clear-cut difference between inter- and intraspecific variability. We tested the ability of these regions to discriminate among closely related species in seven genera of flowering plants with different generation times (trees, perennials, and annuals). To ensure a maximum coverage of intraspecific diversity, and therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…As a consequence, the use of multiple barcode markers consistently improves taxonomic resolution because a particular marker can compensate for the deficits in resolution of its counterparts [7; 9; 10; 15; 17; 18; 19; 20; 21; 22; 23; 24; 25; 26]. This complementarity supports the use of specific barcodes that optimize species resolution for different groups [58; 59]. …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As a consequence, the use of multiple barcode markers consistently improves taxonomic resolution because a particular marker can compensate for the deficits in resolution of its counterparts [7; 9; 10; 15; 17; 18; 19; 20; 21; 22; 23; 24; 25; 26]. This complementarity supports the use of specific barcodes that optimize species resolution for different groups [58; 59]. …”
Section: Discussionmentioning
confidence: 79%
“…However, the same lack of resolution was observed with our ITS2 data and in a more detailed analysis of 22 species [26], indicating that the lack of divergence extends into the nuclear genome. This difficulty in differentiating Salix species using molecular markers may reflect hybridization, introgression, recent speciation, allele surfing via range expansion, and low rates of molecular evolution [52; 59; 67; 68; 69]. More extensive phylogenetic studies targeting nuclear markers or whole plastid genomes are necessary to clarify the processes driving the unusually low divergences in Salix .…”
Section: Discussionmentioning
confidence: 99%
“…was estimated to have diversified from only 3.9 (HPD values: 2.1–6.0) million years onwards [ 40 ]. Incomplete lineage-sorting and interspecific hybridisation events may also contribute to the failure of DNA barcodes to accurately resolve taxa that have only recently diverged [ 55 ]. Additional resolution may be achieved from concatenation of multiple markers [ 56 ], however, this may not always be the case.…”
Section: Discussionmentioning
confidence: 99%
“…Determination accuracy was lower based on our combined (rbcL+matK+ITS) dataset than that of our ITS datasets ( Table 3 ). Other studies that also have found that the concatenation of loci does not always improve resolution power [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA barcoding is a technique, which provides quick identification of species without involving the morphological indication and physiological conditions, of the plant species chosen for study [2]. The plant DNA barcoding studies were initially restricted to the chloroplast genome to understand the variation of its gene sequences of coding matK, rbcL and rpoC1 and non-coding ITS and psbA-trnH [1], team together tested the ability of rpoB,rpoC1,matK and psbA-trnH regions to discriminate among closely related species in seven genera of flowering plants with different generation times (trees, perennials, and annuals). In the study nucleotide variation at chloroplast (Cp) region, loci psbA-trnH and phylogenetic diversity among 24 rice genotypes belonging to Chhattisgarh was analyzed.…”
Section: Resultsmentioning
confidence: 99%